Evaluation of farmers crop production practices that determine Striga gesnerioides infestation of cowpea fields in Nigerian savannas - Dugje, I.Y.; Kamara, A.Y.; Ekeleme, F. (2010)
Striga gesnerioides is considered a major constraint to improving cowpea productivity in the semi arid region of Africa. A field survey was conducted in a farmer participatory process in 100 cowpea fields to determine farmers’ crop production practices that influence infestation by the parasitic weed. Fields with emerged striga plants were sampled in the Northern Guinea Savanna (NGS), and Sudan Savanna (SS). The results showed that prolonged duration of land use for more than 6 years and, the continuous cropping of cowpea increased striga infestation and reduced grain yield, while increased phosphorus levels between 30-45 kg P2O5 ha-1 reduced striga infestations in NGS. The improved and striga resistant cowpea variety (IT97K 499-35) and rotation of cowpea with cereals reduced striga infestations which increased grain yield of cowpea. Increased phosphorus levels of between 30-45 kg P2O5 ha-1 reduced striga infestation and increased grain yield of cowpea in SS, but late planting of sole cowpea fields promoted infestation. Striga counts were generally greater for all the practices in NGS than SS, while grain yield was greater for all the practices in SS than NGS. Increase in period of land use and relay intercropping contributed less to reducing infestation, while Phosphorus fertilizer application, use of resistant variety and rotation contributed more to decrease in infestation and increase in yield in both ecological zones. Therefore, the major factors that promote striga infestation are: prolonged land use, growing varieties that are not resistant to striga, continuous cropping of cowpea, inadequate phosphorus fertilization and late planting of cowpea. Consequently, striga infestations could be reduced through integrated control by combining resistant cowpea varieties, adequate phosphorus fertilizer application, and rotation of cowpea with cereals.